The tsunami history and prehistory of Nuʻu Refuge, Maui, Hawaiʻi - Fisher, Scott; Goff, James; Cundy, Andrew B.; Sear, David (Marine geology, 2025)
In the 21st century tsunamis have claimed the lives of at least 253,000 people globally, making them one of the deadliest natural disasters. In Hawai'i, destructive events occur, on average, every 11 years. This study takes a multi-proxy approach to understand the magnitude and frequency of tsunamis at the Nuʻu Refuge, Kaupō, Maui, Hawai'i. Research there revealed sedimentary evidence of four tsunami or storm events dating from as early as 1837 CE from both local and distant sources. Sedimentary evidence from the wetlands indicates a depositional environment dominated by tsunami inundation coupled with increasing isolation from the sea. Understanding (a) the source, magnitude and frequency of tsunami events and (b) ongoing geomorphological change provides a foundation for developing mitigation strategies to reduce the destructive potential of future tsunamis. •The Hawaiian Islands are subject to frequent tsunami inundation.•The Nuʻu Refuge contains evidence of 5 tsunamis, from the 17th to the 20th century.•Multi-proxy approaches are critical to understanding tsunami deposits.•Tsunami-induced avulsions can result in geomorphological changes to the coast.•Insights into tsunami frequency and intensity can promote mitigation strategies.